Reforming Legal Documentation and Information Governance: Advancing Transparency and Accountability in University Legal Services - Bayangsari Wedhatami; Anhar Dana Putra; Riska Alkadri; Ayup Suran Ningsih; Laga Sugiarto (Universitas Negeri Semarang, 2026)
Transparency and accountability are essential for building trustworthy legal services in universities. Universities are expected to provide accessible legal information while managing legal documents in a clear and responsible way, in line with applicable regulations. In this regard, the way legal documentation and information are governed has a significant impact in shaping the quality of university legal services. Using a qualitative socio-legal approach, the research relies on descriptive analysis based on empirical findings. This study addresses research gaps by mapping the current state of legal documentation governance at universities in Indonesia and proposing a model for managing legal documentation and information through a specialized legal repository. The research shows that stronger legal services can be achieved through better integration of legal documentation systems, the development of the Legal Documentation and Information Network, improved human resource capacity, and regular evaluation. These efforts help make legal services more transparent, accountable, and effective. This study makes a substantive contribution to the field of research. First, it presents a systematic mapping of the state of legal document management systems at Indonesian universities, identifying six structural barriers that have not previously been categorized in the academic literature. Second, this study develops a model and strategies for fostering a culture of legal document management at universities. Overall, this study highlights that strengthening legal documentation and information governance is essential for embedding transparency and accountability in university legal services. This requires not only regulatory compliance but also sustained institutional commitment and practical reforms in implementation.